C5aR and C3aR antagonists each inhibit diet‐induced obesity, metabolic dysfunction, and adipocyte and macrophage signaling. Issue 2 (1st November 2012) - Lim, Junxian; Iyer, Abishek; Suen, Jacky Y.; Seow, Vernon; Reid, Robert C.; Brown, Lindsay; Fairlie, David P.
Abstract : Mammalian survival depends on metabolizing nutrients, storing energy, and combating infection. Complement activation in blood triggers energy‐depleting immune responses to fight infections. Here we identify surprising energy‐conserving roles for complement proteins C5a and C3a and their receptors, C5aR and C3aR, roles that are contraindicated in complement biology. Rats fed a high‐carbohydrate high‐fat diet developed obesity, visceral adiposity, adipose inflammation, glucose/insulin intolerance, and cardiovascular dysfunction that correlated with increased plasma C3a, adipose C5aR, and C3aR. These in vivo changes were dramatically attenuated by receptor‐selective antagonists of either C5aR (5 mg/kg/d p.o.) or C3aR (30 mg/kg/d p.o.), which both reduced proinflammatory adipokines and altered expression of inflammatory genes in adipose tissue. In vitro C5a and C3a (100 nM) exhibited novel insulin‐like effects on 3T3‐L1 adipocytes, promoting energy conservation by increasing glucose and fatty acid uptake while inhibiting cAMP signaling and lipolysis, and induced PGE2 release from macrophages, effects all blocked by each respective antagonist (10 μM). These studies reveal important new links between complement signaling and metabolism, highlight new complement functions on adipocytes and in adipose tissue, demonstrate how aberrant immune responses may exacerbate obesity and metabolic dysfunction, and show that targeting C3aR or C5aR with antagonists is a new strategy for treating metabolic dysfunction.—Lim, J., Iyer, A., Suen, J. Y., Seow, V., Reid, R. C., Brown, L., Fairlie, D. P. C5aR and C3aR antagonists each inhibit diet‐induced obesity, metabolic dysfunction, and adipocyte and macrophage signaling. FASEB J. 27, 822–831 (2013). www.fasebj.org